AUDIT ENERGI PADA BANGUNAN GEDUNG TEKNIK KENDARAAN RINGAN SMKN 2 SUMBAWA BESAR - prasetyo, bagas; Aulia, Masyitah; Darmawan , Indra; Andriani, Titi; Indah Kencana, Putri (Program Studi Teknik Elektro, 2024)
Electric power is a type of energy used to operate electrical equipment. This energy is stored in electric currents in units of amperes (A) and voltages in units of volts (V). The use of electrical energy is used for various purposes such as driving motors, lighting lamps, heating or cooling equipment, and driving other mechanical equipment. Electrical energy is used in various sectors, including households, offices, industry, rail transportation, street lighting, and various other activities such as cooking and heating. The purpose of this study is to determine the consumption of electrical energy in the Light Vehicle Engineering building at SMKN 2 Sumbawa Besar and to be able to recommend solutions so that the use of electrical energy can be more cost-effective. The method used in this study is a mixed method (Mixed Method Research), which combines elements of qualitative and quantitative methods. The process of observing and conserving energy involves steps such as an energy audit. The results of this study were that the value of energy consumption intensity (IKE) in the light vehicle engineering building in the previous year was 13.66 kWh/m2/year, while the IKE value for the room was 10.14 kWh/m2/month.